Proceedings of the 10th International Congress on the Archaeology of the Ancient Near East: 25-29 April 2016, Vienna - Horejs, Barbara; Schwall, Christoph; Müller, Vera; Luciani, Marta; Ritter, Markus; Guidetti, Mattia; Salisbury, Roderick B.; Höflmayer, Felix; Bürge, Teresa (Harrassowitz Verlag, 2018)
Transformation & migration / Barbara Horejs and Christoph Schwall -- Archaeology of religion & ritual / edited by Vera Müller -- Images in context: agency, audiences & perception / edited by Marta Luciana -- Islamic archaeology / edited by Markus Ritter and Mattia Guidetti.